The moderation effect of the Dark Tetrad on the relationship between fear of negative evaluation and academic dishonesty - Lee, Darian Jun Jie (Nanyang Technological University, 2023)
The study aims to investigate the relation between fear of negative evaluation and academic dishonesty and proposes a moderator model in which each of the Dark Tetrad traits moderates the relation between fear of negative evaluation and academic dishonesty. For the pilot study, a total of 94 participants were recruited across universities in Singapore to take part in a vignette task. The purpose of the vignette task was to measure how effective vignette tasks were at priming fear of negative evaluation in participants. Results showed that the vignette task was significant in priming fear of negative evaluation in the experimental group as compared to the control group. For the main study, a total of 63 undergraduates were recruited across universities in Singapore to take part in the study. Items from the Short Dark Tetrad, modified items from Academic Dishonesty Scale, and modified items of the Brief version of the Fear of Negative Evaluation Scale – Revised and Marlowe-Crowne Social Desirability Scale were included in the study which was administered remotely. Results of the study showed that there was no significant relationship between fear of negative evaluation and academic dishonesty. The Dark Tetrad traits were also found to not significantly moderate the relation between fear of negative evaluation and academic dishonesty.